2021
DOI: 10.1007/s41826-021-00041-x
|View full text |Cite
|
Sign up to set email alerts
|

The Majiayao to Qijia transition: exploring the intersection of technological and social continuity and change

Abstract: The transition between the Majiayao (5300-4000 BP) and Qijia (4200-3500 BP) "cultures" in what is now northwestern China's Gansu Province has typically been defined by major technological changes in pottery forms, subsistence practices, and site locations. These changes are thought to have been driven by a combination of climate change induced cooling and drying as well as human migration into the region from areas further east. Based on our review of literature on the topic, as well as recent fieldwork in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…The use of pottery at funeral events for building prestige and power in the northern Tao River Valley, however, seems less likely. While at sites such as the late Majiayao cemetery at Liuwan and the Qijia cemetery of Mogou, there is some evidence of social competition and even incipient hierarchy (Allard 2002; Dittmar et al 2019), at the sites included in the present study, graves and grave assemblages are all relatively similar in size and contents (see Womack et al 2021 for details). Therefore, while it is possible that some funeral gifting or feasting at these sites may have been competitive in nature, it was at most small-scale, and thus it appears more likely that pottery transfers were important for tying together communities.…”
Section: Discussion: Ceramic Circulation In the Tao River Valley And ...mentioning
confidence: 56%
See 1 more Smart Citation
“…The use of pottery at funeral events for building prestige and power in the northern Tao River Valley, however, seems less likely. While at sites such as the late Majiayao cemetery at Liuwan and the Qijia cemetery of Mogou, there is some evidence of social competition and even incipient hierarchy (Allard 2002; Dittmar et al 2019), at the sites included in the present study, graves and grave assemblages are all relatively similar in size and contents (see Womack et al 2021 for details). Therefore, while it is possible that some funeral gifting or feasting at these sites may have been competitive in nature, it was at most small-scale, and thus it appears more likely that pottery transfers were important for tying together communities.…”
Section: Discussion: Ceramic Circulation In the Tao River Valley And ...mentioning
confidence: 56%
“…Whether vessels and their contents were brought as gifts or were exchanged for other items is unclear, as are any assumptions of their relative value or meaning to Majiayao and Qijia-period peoples. Other goods, such as deer-antler tools in Majiayao deposits at Dayatou (Brunson et al 2020) and jade and bronze items during the Qijia-period (Jaang 2015; Womack et al 2021), may also have circulated in these networks.…”
Section: Discussion: Ceramic Circulation In the Tao River Valley And ...mentioning
confidence: 99%
“…BC (3581-3381 cal. BP) based on 12 dates from two pits (Brunson et al, 2020;Womack et al, 2021). The data from Qijiaping imply a flourishing of Qijia culture in the Tao river region in a 150year period, and combined with other Qijia culture contexts in the Tao River valley, such as the site of Mogou (Gansu & Xibei, 2009), these data show an intensity of occupation in the Tao river valley at the time when others have suggested that Qijia is collapsing, possibly because people may have migrated there from other regions.…”
Section: Second Millennium Bc Northwest China: Climate Change and Economic Consequencesmentioning
confidence: 99%
“…BP. Following the occupation of Qijia culture sites in this valley, including the culture type-site of Qijiaping (Womack et al, 2017(Womack et al, , 2021, the area is occupied by communities creating ceramics of the Xindian cultural tradition. The distribution of Xindian sites displays a relatively clear geographical pattern in the Tao River valley.…”
Section: Second Millennium Bc Northwest China: Climate Change and Economic Consequencesmentioning
confidence: 99%
See 1 more Smart Citation